Hazardous Waste Management in the Cement Industry for Alternative Raw Material (ARM) or Alternative Fuel (AF) - Setiaji, Nurul Faizah; Sarwono, Ariyanti; Suryawan, I Wayan Koko (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
Hazardous waste from the cement industry can pollute the environment and human health. The use of cement industry waste can be done to minimize this impact. This study aims to analyze the initial conditions of hazardous waste management in the cement industry and its potential utilization. This research was conducted by field observation through three stages, namely the stages of preparation, implementation, and preparation of reports. The XYZ cement industry has two procurement schemes, polutter payment and purchase. The XYZ cement industry permits hazardous waste as an alternative raw material (ARM) for fly ash, bottom ash, paper sludge, drilling cutting, crude oil, contaminated soil, and bleaching earth/eco oil, EAF (electric arc), and dust furnaces. Meanwhile, alternative fuel (AF) consists of used bag cloth, majun (contimated textile waste), used oil, kluber, used grease, resin, and pure SBE (spent bleaching earth).